What lies behind the strength, sensitivity, and precision of the human hand? What lies behind the strength, sensitivity, and precision of the human hand? (Health and Biosciences, 2025)
The teaching of Biology is often considered challenging for students due to the complexity of scientific terms and the difficulty of visually representing structures and processes. Furthermore, teacher-centered approaches contribute to weaknesses in teaching practice. Addressing this content through an investigative approach provides students with a more contextualized and, therefore, more meaningful understanding. This report aimed to describe the teaching actions and impressions from an investigative activity in which students were invited to identify the tissues that make up the hand, investigate their integration, and understand the contribution of each to the different characteristics of the human hand. Five fifty-minute lessons were used, during which students were divided into three groups and carried out the following activities: formulating hypothesis based on a guiding question - which gave the title to this report - preparing questions for an interview with a healthcare professional, comparing data, and presenting the results obtained. Despite some challenges, such as the novelty of investigative activity, difficulty in maintaining focus, and developing independent thinking, students concluded that hand strength is influenced by several factors, including anatomy, physiology, and the nervous system. Muscles, tendons, and ligaments that make up the hands, the nervous system that controls movements, muscle size and composition, training and practice of activities involving hand use, genetics, and the individual’s overall health were identified as key elements.
Keywords: investigative teaching; basic education; biological tissues